Clinical manifestations and epidemiology of adolescent tuberculosis in Ukraine - Chiang, Silvia S. (ERJ Open Res, 2020)
BACKGROUND: During adolescence, childhood and adult forms of tuberculosis (TB) overlap, resulting in diverse disease manifestations. Knowing which patient characteristics are associated with which manifestations may facilitate diagnosis and enhance understanding of TB pathophysiology. METHODS: In this cross-sectional study, we included 10–19-year-olds in Ukraine's national TB registry who started TB treatment between 2015 and 2018. Using multivariable regression, we estimated associations between patient characteristics and four presentations of TB: pleural, extrathoracic, cavitary and rifampicin-resistant (RR). We also described the epidemiology of adolescent TB in Ukraine. RESULTS: Among 2491 adolescent TB cases, 88.4% were microbiologically confirmed. RR-TB was confirmed in 16.9% of new and 29.7% of recurrent cases. Of 88 HIV-infected adolescents, 59.1% were not on antiretroviral therapy at TB diagnosis. Among 10–14-year-olds, boys had more pleural disease (adjusted OR (aOR) 2.12, 95% CI: 1.08–4.37). Extrathoracic TB was associated with age 15–19 years (aOR 0.26, 95% CI: 0.18–0.37) and HIV (aOR 3.25, 95% CI: 1.55–6.61 in 10–14-year-olds; aOR 8.18, 95% CI: 3.58–17.31 in 15–19-year-olds). Cavitary TB was more common in migrants (aOR 3.53, 95% CI: 1.66–7.61) and 15–19-year-olds (aOR 4.10, 95% CI: 3.00–5.73); among 15–19-year-olds, it was inversely associated with HIV (aOR 0.32, 95% CI: 0.13–0.70). RR-TB was associated with recurrent disease (aOR 1.87, 95% CI: 1.08–3.13), urban residence (aOR 1.27, 95% CI: 1.01–1.62) and cavitation (aOR 2.98, 95% CI: 2.35–3.78). CONCLUSIONS: Age, sex, HIV and social factors impact the presentation of adolescent TB. Preventive, diagnostic and treatment activities should take these factors into consideration.